Phytochemical Screening and Mucoadhesive Microsphere-Based Delivery of Folk Medicinal Plant Extracts for Neuroprotective Applications. - Singh, Pinky; Mourya, Rita; Sharma, Pragya; Kannouje, Hritika; Srivastava, Manisha (Journal of Neonatal Surgery, 2025)
Background: Neurodegenerative diseases present major therapeutic challenges with limited treatment options. Folk medicinal plants contain promising neuroprotective compounds, but poor bioavailability restricts clinical application. This study developed mucoadhesive microsphere delivery systems to enhance bioavailability of phytochemicals from traditional neuroprotective plants. Methods: Five folk medicinal plants (Bacopa monnieri, Centella asiatica, Withania somnifera, Convolvulus pluricaulis, Evolvulus alsinoides) underwent successive extraction and comprehensive phytochemical screening using spectrophotometric, HPLC, and GC-MS analyses. Neuroprotective activity was evaluated in SH-SY5Y cells against H₂O₂-inducedoxidative stress. Chitosan-based mucoadhesive microspheres were prepared by ionotropic gelation and characterized for drug delivery parameters.Results: Methanolic extracts yielded maximum phytochemicals (9.2-14.3%). Centella asiatica showed highest phenolic content (72.1 ± 3.8 mg GAE/g) and antioxidant activity (DPPH IC₅₀: 38.2 ± 2.1 μg/mL). Strong correlation existed between phenolic content and antioxidant activity (r = 0.892, p < 0.01). All extracts demonstrated significant neuroprotection (50.1-69.5%) against oxidative damage. Optimized microspheres achieved 186.3 ± 12.4 μm particle size, 78.9 ± 4.2% encapsulation efficiency, and sustained pH- responsive release over 12 hours. Enhanced intestinal permeability (1.8-2.0 fold) and bioavailability (1.74-fold) were achieved versus free extracts. Conclusion: Integration of phytochemical screening with mucoadhesive microspheretechnology successfully addresses bioavailability limitations of traditional neuroprotective medicines, providing a framework for evidence-based phytotherapeutic development against neurodegenerative diseases.